Private Enterprise vs. Government Control: An Organizationally Dynamic Comparison - Pavel Pelikan (The Research Institute of Industrial Economics (IUI), 1985)
It is noted that modern economics cannot decide which economic system is the best way of organizing production. In particular, support is given to Nelson (1981) who claims that modern economics does not provide any substantial argument in favor of private enterprise being the best. However, rather than concluding that government control or socialist planning could do at least as well, this essay explores the alternative hypothesis that the organizationally static framework of most of modern economics is too narrow to see the entire truth. Connected to Schumpeter's and Hayek's approaches, an organizationally dynamic analytical framework is outlined and shown to reveal important advantages of private enterprise, in particular of contestable private enterprise with equitable risk assignment. This argument is qualified by showing that even such a system may suffer from organization failures which can be alleviated by selection-neutral industrial policy, including government entrepreneurship on underdeveloped markets.
Keywords: D23; D70; L10; 330; Organising production; public vs private enterprise; dynamic framework